A role in vacuolar arginine transport for yeast Btn1p and for human CLN3, the protein defective in Batten disease - Kim, Yoojin (National Academy of Sciences, 2003)
In Saccharomyces cerevisiae, transport of arginine into the vacuole has previously been shown to be facilitated by a putative H(+)/arginine antiport. We confirm that transport of arginine into isolated yeast vacuoles requires ATP and we demonstrate a requirement for a functional vacuolar H(+)-ATPase. We previously reported that deletion of BTN1 (btn1-Δ), an ortholog of the human Batten disease gene CLN3, resulted in a decrease in vacuolar pH during early growth. We report that this altered vacuolar pH in btn1-Δ strains underlies a lack of arginine transport into the vacuole, which results in a depletion of endogenous vacuolar arginine levels. This arginine transport defect in btn1-Δ is complemented by expression of either BTN1 or the human CLN3 gene and strongly suggests a function for transport of, or regulation of the transport of, basic amino acids into the vacuole or lysosome for yeast Btn1p, and human CLN3 protein, respectively. We propose that defective transport at the lysosomal membrane caused by an absence of functional CLN3 is the primary biochemical defect that results in Batten disease.